EDUKASI KESEHATAN PADA ANAK: PENGENALAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DENGAN VIDEO ANIMASI - Estin Gita Maringga; Endah Luqmanasari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Education about health in early childhood is needed as a way to provide information to the child about Healthy Life Behavior (PHBS). Health education that has been given is expected to improve the health quality of a child. The quality of children's health at an early will affect the quality of children's growth and development in the future. The purpose of this community service activity is to introduce PHBS to early childhood in the form of 6 steps of hand washing, how to brush teeth properly, and nutritious food using animated videos. The target of this service activity is early childhood children at PAUD Kusuma Harapan Darungan Village, Kediri. The method of activity is carried out in the form of counseling using animated videos, demonstrations using phantom, and question and answer activities. This service activity begins with an oral pre-test for the target group about hand washing, how to brush teeth correctly, and nutritious food. Furthermore, health education was carried out using animated videos and then followed by demonstrations to the target group. The evaluation of this activity was carried out at the end of the event by giving verbal questions to the target group and practicing hand washing and proper brushing of teeth in front of the class. The results achieved in this activity are that there is a change in the knowledge of the target group on the behavior of washing hands in 6 steps, brushing teeth properly, and eating nutritious food before and after health education is given. PHBS needs to be introduced early to children because in toddlerhood there is a golden age period that makes it easier for children to absorb information and imitate the behavior they encounter.